2012
DOI: 10.1371/journal.pone.0046902
|View full text |Cite
|
Sign up to set email alerts
|

Exploring PHD Fingers and H3K4me0 Interactions with Molecular Dynamics Simulations and Binding Free Energy Calculations: AIRE-PHD1, a Comparative Study

Abstract: PHD fingers represent one of the largest families of epigenetic readers capable of decoding post-translationally modified or unmodified histone H3 tails. Because of their direct involvement in human pathologies they are increasingly considered as a potential therapeutic target. Several PHD/histone-peptide structures have been determined, however relatively little information is available on their dynamics. Studies aiming to characterize the dynamic and energetic determinants driving histone peptide recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 55 publications
2
66
0
Order By: Relevance
“…Indeed, a substitution of the cysteine with tyrosine predicts disruption of PHD1 folding ( Figure 3B; Chakravarty et al, 2009). Additional structural analyses revealed that many of the reported missense mutations changed amino acids that were conserved among different species (Figures 3B and S5;Bjö rses et al, 2000;Org et al, 2008;Spiliotopoulos et al, 2012) and could similarly affect the Zn 2+ -binding or folding of the domain.…”
Section: Dominant-negative Mutants Physically Co-localize With Wt Airementioning
confidence: 96%
“…Indeed, a substitution of the cysteine with tyrosine predicts disruption of PHD1 folding ( Figure 3B; Chakravarty et al, 2009). Additional structural analyses revealed that many of the reported missense mutations changed amino acids that were conserved among different species (Figures 3B and S5;Bjö rses et al, 2000;Org et al, 2008;Spiliotopoulos et al, 2012) and could similarly affect the Zn 2+ -binding or folding of the domain.…”
Section: Dominant-negative Mutants Physically Co-localize With Wt Airementioning
confidence: 96%
“…Binding free energy calculations of AKR1B10 and reference inhibitor/hit compounds The Molecular Mechanics/Poisson-Boltzmann Surface Area (MM/PBSA) method was used to compute the binding free energies of the protein-ligand complexes, as described earlier [38][39][40] . For this purpose, 20 snapshots of each complex (AKR1B10 and reference inhibitor/hit compounds) were chosen evenly from 0 to 10 ns MD trajectories according to earlier reports [38,41] .…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The long-range electrostatic interactions were treated with the Particle Mesh Ewald (PME) technique while non-bond interactions were truncated with an 1.2-nm cutoff. The MM/PBSA approach was applied to binding energy calculations using GMXAPBS tool 52 , which is a Bash/Perl script to facilitate the interface between GROMACS and APBS 53 . The average of last 15 ns MD simulations (600 frames) was considered to calculate the binding energy and the entropic term was neglected.…”
Section: Methodsmentioning
confidence: 99%